An Evaluation of Stevia rebaudiana Leaf-Axillary Shoot Formation, Cultured in MS Medium Supplemented with IAA-BAP and MS Medium Supplemented with Kinetin - Andira Rahmawati; Victor Emmanuel; Iriawati Iriawati; Khalilan Lambangsari; Rizkita Rachmi Esyanti; Roohaida Othman; Aldo Nathan Dela Simamora; Bugy Suwito (School of Life Sciences and Technology, Institut Teknologi Bandung, 2023)
Stevia rebaudiana leaves can be used as a sweetener alternatives because they contain steviol glycoside derivative compounds, including steviosides and rebaudioside-A. Propagation of Stevia is more optimally carried out using in vitro culture when compared to conventional propagation through seeds or cuttings. This study aimed to evaluate the formation and growth of Stevia shoots and leaves in MS medium containing a mixture of IAA and BAP with MS medium containing kinetin only, as well as evaluating the use of a liquid medium containing kinetin. Stevia was initiated from apical shoot then grown in MS medium containing a mixture of IAA and BAP with MS medium containing kinetin only. Stevia was subcultured every 4 weeks. Several parameters measured were number of axillary shoots and number of leaves. It was transferred into a liquid medium for 7 days. The results showed that the formation and growth of axillary buds and leaves at the initiation stage were better in medium containing IAA and BAP compared to medium containing single hormone kinetin. At the stage of shoot multiplication and maintenance, cultivation in semi-solid medium containing kinetin showed more leaves and axillary shoots compared to that cultivated in semi-solid medium with the addition of IAA and BAP. Plants acclimatized in liquid medium supplemented with 1 ppm kinetin showed fast plant growth but were not accompanied by sturdy stem growth. The presence of brownish color on certain parts of the plant such as in some leaves and stems was also observed.